Characteristics and technological needs of beekeepers in the south-central region of Jalisco - Saavedra Jiménez, Luis Antonio; Sánchez Gómez, Julia; Vázquez Alfaro, Marisol; Alaníz Gutiérrez, Luis; González Álvarez, Vicente Homero (Acta Universitaria, 2022)
To analyze the characteristics, training, and technology needs, as well as the problems faced by beekeepers in the south-central region of Jalisco, 33 beekeepers, selected by directed sampling, from the municipalities of Guadalajara, Zacoalco de Torres, and Zapotiltic, were interviewed, between November 2019 and February 2020. It was found that, on average, the age of participants was 57 years with 23 years of experience in beekeeping and 394 hives per beekeeper. Honey production represents the main activity for those with more than 70 hives. The annual yield per hive ranged between 10 kg and 30 kg. A total of 18 aspects related to the need for training and technology were identified, where marketing and beekeeping equipment stood out. Likewise, 23 problems limit this activity, especially pests, diseases, and deforestation. It is concluded that beekeepers present heterogeneous characteristics and productive conditions that correspond to the needs of training and technology.